Reporting a Case Analysis of Gaea Company - Extra Virgin Olive Oil - Alexandra Maria Mavroeidakou (Insights into Economics and Management Vol. 8, 2021)
Without a doubt, the olive oil industry is a traditional industry that has undergone many breakthroughs in recent years as many companies try to combine the traditional method used in previous years with the innovations that bring about the rapid advancement of technology. In this paper, it will be presented the historical background of the Gaea Company which is the main subject of this study, the description of the product and the major competition of this brand so as to be constructed an integrated marketing plan which will involve the objectives of the company, its target segments and a purposed value proposition for it. Next to that, it will be analyzed the marketing strategy that has adopted the company in the light of the product, the place, the price, and the promotion. Armed with this information, it will be evaluated the product’s current marketing strategy and will be given recommendations that may be helpful for the development of the company having always as benchmark the best practices applied in the marketing management. Although there are many things that Gaea should reconsider so as to reach its ambitious goals, the guidelines that direct its plan ensure that Gaea will have a promising future in the long run.